The Effectiveness of Online Learning for Mathematics Students during the Covid-19 Pandemic - Ilmadi Ilmadi; Ramzil Huda Zarista; Aden Aden; Gerry Sastro (Mathematics Education Study Program, 2020)
The spread of the Covid-19 virus globally continues to grow. The impact felt by Indonesia in addition to the many positive cases, economic, social and educational system problems. The learning process that has been carried out face-to-face has become undisturbed, so that the learning process changes its function to online learning. The purpose of this research is to obtain information on how to describe the implementation process of learning for students of the Pamulang University Mathematics Study Program during the Covid-19 pandemic as an effort for Higher Education to stop and break the chain of spreading covid-19. The research subjects were students of the Mathematics Study Program. Data processing was carried out by interviewing through cloud meetings and questionnaire response sheets using the google format. Interviews and questionnaire sheets were conducted with questions that were compiled and developed with related literature. Miles & Huberman's interactive analysis techniques were used in this study. This study obtained the results, namely, (1) students already have basic learning facilities such as leptops, computers, android-based mobile phones and internet networks; (2) The learning process has not been maximally carried out yet; (3) Lack of supervision from both lecturers and parents during the lecture or learning process; (4) The online learning process has the advantage of flexibility in time, encourages and trains students to study independently.